The potential implications of reclaimed wastewater reuse for irrigation on the agricultural environment: the knowns and unknowns of the fate of antibiotics and antibiotic resistant bacteria and resistance genes – a review - Christou, Anastasis (2017)
The use of reclaimed wastewater (RWW) for the irrigation of crops may result in the continuous exposure of the agricultural environment to antibiotics, antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs). In recent years, certain evidence indicate that antibiotics and resistance genes may become disseminated in agricultural soils as a result of the amendment with manure and biosolids and irrigation with RWW. Antibiotic residues and other contaminants may undergo sorption/desorption and transformation processes (both biotic and abiotic), and have the potential to affect the soil microbiota. Antibiotics found in the soil pore water (bioavailable fraction) as a result of RWW irrigation may be taken up by crop plants, bioaccumulate within plant tissues and subsequently enter the food webs; potentially resulting in detrimental public health implications. It can be also hypothesized that ARGs can spread among soil and plant-associated bacteria, a fact that may have serious human health implications. The majority of studies dealing with these environmental and social challenges related with the use of RWW for irrigation were conducted under laboratory or using, somehow, controlled conditions. This critical review discusses the state of the art on the fate of antibiotics, ARB and ARGs in agricultural environment where RWW is applied for irrigation. The implications associated with the uptake of antibiotics by plants (uptake mechanisms) and the potential risks to public health are highlighted. Additionally, knowledge gaps as well as challenges and opportunities are addressed, with the aim of boosting future research towards an enhanced understanding of the fate and implications of these contaminants of emerging concern in the agricultural environment. These are key issues in a world where the increasing water scarcity and the continuous appeal of circular economy demand answers for a long-term safe use of RWW for irrigation.